Anonymous

# Ag + NO3 -  Ag + + NO?

Step 1: What substance is reduced?

Step 2: What substance is oxidized?

Step 3: What is the half reaction for oxidation?

Step 4: What is the half reaction for reduction?

Step 5: What is the net balanced equation?

Step 6: What is the reduced equation?

Relevance

Ag + (NO3)-1 --> Ag+1 & NO

Step 1: What substance is reduced?

the nitrogen in (NO3)-1

from +5 to +2

Step 2: What substance is oxidized?

the Ag metal from zero to +1

Step 3: What is the half reaction for oxidation?

Ag --> Ag+1 & 1 e-

Step 4: What is the half reaction for reduction?

(NO3)-1 & 3 e- --> NO

Step 5: What is the net balanced equation?

3Ag + 1 (NO3)-1 --> 3Ag+1 & 1 NO

& if you want the rest, it would also use:

3Ag + 1 (NO3)-1 & 4 H+ --> 3Ag+1 & 1 NO & 2H2O

Step 6: What is the reduced equation?

would you email an example showing me what typically this would be...

because I see how to reduce that equation any more than it is...

unless you mean:

3Ag + 1 N+5 --> 3Ag+1 & 1 N+2